Determination of Tramadol and Fluoxetine in Biological and Water Samples by Magnetic Dispersive Solid-Phase Microextraction (MDSPME) with Gas Chromatography – Mass Spectrometry (GC-MS). (24th March 2021) - Sefaty, Banafsheh; Masrournia, Mahboubeh; Es'haghi, Zarrin; Bozorgmehr, Mohammad Reza
Abstract: In the present study, magnetic dispersive solid-phase microextraction coupled with gas chromatography – mass spectrometry was developed to simultaneously determine tramadol and fluoxetine in water and biological samples. Magnetic Fe3 O4 @graphene oxide was synthesized based on a modified Hummer's method and utilized as an efficient sorbent for the determination of tramadol and fluoxetine. The main factors influencing the microextraction efficiency of the analytes were optimized by the design of experiment including Plackett-Burman design and central composite design. The developed analytical method demonstrated a very wide linear range of approximately three orders of magnitude, low limits of detection less than or equal to 0.088 ng mL −1 and limits of quantitation less than or equal to 0.29 ng mL −1, good relative standard deviations less than or equal to 4.08% ( n = 5), and high enrichment factors greater than or equal to 59.96 for the determination of tramadol and fluoxetine. Other advantages of the developed method include low cost, reduced use of sorbent and sample solution, high enrichment factors, simple sorbent preparation, rapid analysis time, and high extraction recoveries for the samples. Moreover, the determination of tramadol and fluoxetine in urine, plasma, hair, and groundwater indicated that the presented method is suitable for the determination of the analytes in biological and water samples with excellent recoveries and reproducibility.